Effect of plant growth regulators on growth and lipid accumulation of microalgal Haematococcus pluvialis Flotow in two-stage culture - Dong Phuong, Nguyen Tran; Ai Thuy, Le Huyen; Trang Viet, Bui (Vietnam Journal of Biotechnology, 2020)
Haematococcus pluvialis cells were cultured in aerated liquid Bold’s Basal medium in two-stage (initial stage during in 7 weeks for increased biomass growth and second stage during in 3 weeks for increased lipid accumulation) with different volumes 250 mL, 10 L, and 1,000 L. With a volume of 250 mL, the medium was supplied with benzyl adenine (BA), indole-3-acetic acid (IAA) or gibberellic acid (GA3) at concentration from 0.1 - 0.2 mg/L in initial stage and IAA or GA3 at concentration from 0.1 - 0.2 mg/L in second stage. After 10 weeks of culture, results showed that supplement of 0.1 mg/L BA in initial stage and 0.125 mg/L IAA in second stage increased cell density, and microalgal cells had green color with a spherical shape. On the contrary, supplement of 0.15 mg/L IAA in initial stage and 0.175 mg/L GA3 in second stage increased lipid accumulation, and microalgal cells had red color with a spherical shape. With a volume of 10 L, the medium was supplied with 0.1 mg/L BA in initial stage, and treated with separation or combination from 2 - 3 of these factors (nitrogen starvation, 0.5% NaCl, 4.98 mg/L FeSO4) were applied in second stage. The result showed that the cultures was treated with nitrogen starvation increased dry biomass and biofuel, but treated with 4.98 mg/L FeSO4 only increased biofuel. With a volume of 1,000 L, microalgal cells were cultured in BB liquid medium in initial stage, and treated with 4.98 mg/L FeSO4 increased fresh 78.67 mg/mL and dry biomass 2.05 mg/L and total lipid content 28.24 %/ DW.